Identifying and prioritizing the factors influencing the success of science and technology foresight in the field of economy - Afsaneh Raieninezhad (Management Science Letters)
Promoting complex global environment, tremendous growth and increase of network communication technology in the world, strategic planning and foresight activities in science and technology have become very important. Gradually, organizations and businesses are realizing the importance of foresight; many organizations attempt to execute such activities. However, this concept is not still well known in our country and among our organizations. Therefore, recognizing the factors influencing the success of this concept is a kind of issues that the organizations and activists are faced. Thus, this research seeks to identify and to rank the factors, particularly in the areas of economy, and it has developed five hypotheses. In this paper, factors affecting the success of foresight are given in four groups of rational, structure, scope, and results. Data collection for this study is a questionnaire and the binomial tests, Pearson correlation and Friedman test have been used to prove the hypothesis. According to the analysis of data obtained from the questionnaire conducted by SPSS software, all research hypotheses were confirmed. It also became clear that the rational component had the greatest impact on the future success of science and technology in the field of economic.